The Swedish FrameNet++ : Harmonization, Integration, Method Development and Practical Language Technology Applications. - Dannélls, Dana. (Natural Language Processing Series, 2021)
Large computational lexicons are central NLP resources. Swedish FrameNet++ aims to be a versatile full-scale lexical resource for NLP containing many kinds of linguistic information.